Evaluation of abnormal uterine bleeding with transvaginal sonography and hysteroscopy in perimenopausal women - Choudhary, Jaya; Acharya, Veena; Jain, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding is defined as any deviation from the normal menstrual cycle this include change in regularity, frequency of menses, duration or amount of bleeding during or in between periods. Objective of present study was to evaluate abnormal uterine bleeding with transvaginal sonography and hysteroscopy in perimenopausal women. Methods: This study is conducted on women presenting to the gynecological OPD with complain of abnormal uterine bleeding in perimenopausal age group. A total of 50 patients were subjected to transvaginal sonography and Diagnostic hysteroscopy. Results: On TVS, out of total 50 patients, 50% patient showed normal endometrial finding. 24% Patient showed Endometrial hyperplasia, 14% Endometrial Polyp, 8% Submucosal fibroid, 4% Adenomyosis. On TVS, out of total 50 patient, 50% patient showed normal endometrial finding. 24% Patient showed endometrial hyperplasia, 14% endometrial Polyp, 8% submucosal fibroid, 4% adenomyosis. Out of total 50 patients, 28 (56%) showed normal endometrial finding.20% cases showed endometrial Hyperplasia, 16% showed endometrial Polyp, 8% showed submucosal fibroid. Sensitivity, specificity, PPV, NPV of endometrial hyperplasia – 81.81%, 92.3%, 75%, 94.73% respectively. Conclusions: Transvaginal sonography has a moderate diagnostic accuracy in detecting endometrial hyperplasia and other intrauterine pathology. TVS is safe, acceptable and easily available & is noninvasive. It should be used as 1st line diagnostic tool in patients with AUB in perimenopausal women. Hysteroscopy has important tool in the diagnosis of various endometrial and intrauterine lesions TVS and hysteroscopy should be employed hand in hand in evaluation of AUB.